Systematic approaches to a successful literature review - Booth, Andrew, 1961-; Papaioannou, Diana; Sutton, Anthea (London : SAGE, 2012)
'Reviewing the literature is an essential part of every research project. This book takes you step-by-step through the process of approaching your literature review systematically, applying systematic principles to a wide range of literature review types. Through numerous examples, case studies and exercises, the book covers often neglected areas of literature review such as concept analysis, scoping and mapping'--Jacket.
Includes bibliographical references and index.
Keywords: Research -- Methodology